Development and evaluation of a web-based diet quality screener for vegans (VEGANScreener): a cross-sectional, observational, multicenter, clinical study - Asif, Tooba; Ouřadová, Anna; Martínez Tabar, Ainara; Bullón-Vela, Vanessa; Müller, Sandra; Dietrich, Joelina; Keller, Vanessa; Heniková, Marina; Selinger, Eliška; Herter-Aeberli, Isabelle; Wakolbinger, Maria; De Keyzer, Willem; et al. (Frontiers in Nutrition, 2024)
Consumption of plant-based diets, including vegan diets, necessitates attention to the quality of the diet for the prevention and early detection of nutritional deficiencies. Within the VEGANScreener project, a unique brief screening tool for the assessment and monitoring of diet quality among vegans in Europe was developed. To provide a standardized tool for public use, a clinical study will be conducted to evaluate the VEGANScreener against a reference dietary assessment method and nutritional biomarkers. An observational study is set to include 600 participants across five European sites – Belgium, Czech Republic, Germany, Spain, and Switzerland. In total, 400 self-reported vegans (≥2 years on a vegan diet), and 170 self-reported omnivore controls will be examined, aged between 18 and 65 years, with males and females being equally represented in a 1:1 ratio for two age groups (18-35 and 36-65 years). Participants with diseases affecting metabolism and intestinal integrity will be excluded. The clinical assessment will include a structured medical history, along with taking blood pressure and anthropometric measurements. Blood and urine will be sampled and analyzed for a set of dietary biomarkers. Metabolomic analyses will be conducted to explore potential novel biomarkers of vegan diet. Moreover, saliva samples will be collected to assess the metabolome and the microbiome. Participants will receive instructions to complete a nonconsecutive 4-day diet record, along with the VEGANScreener, a socio-demographic survey, a well-being survey, and a FFQ. To evaluate reproducibility, the VEGANScreener will be administered twice over a three-weeks period. Among vegans, the construct validity and criterion validity of the VEGANScreener will be analyzed through associations of the score with nutrient and food group intakes, diet quality scores assessed from the 4-day diet records, and associations with the dietary biomarkers. Secondary outcomes will include analysis of dietary data, metabolomics, and microbiomes in all participants. Major nutrient sources and variations will be assessed in the sample. Exploratory metabolomic analysis will be performed using multivariable statistics and regression analysis to identify novel biomarkers. Standard statistical models will be implemented for cross-sectional comparisons of geographical groups and vegans versus omnivores.